Ampelographic and Molecular Characterisation of Aglianico Accessions (Vitis vinifera L.) Collected in Southern Italy - Alba, V.; Anaclerio, A.; Gasparro, M.; Caputo, A.R.; Montemurro, C.; Blanco, A.; Antonacci, D. (South African Journal of Enology and Viticulture, 2016)
To characterise 31 different Aglianico accessions randomly collected in Southern Italy, 30 ampelographic descriptors, 13 SSRs and 10 AFLP primer combinations were analysed. An appreciable variation of ampelographic descriptors was revealed mainly by mature leaf traits, while very few variations were recorded for shoot and berry traits. Similarly, all SSR loci revealed molecular monomorphism and AFLPs with a very high genetic similarity (Dice coefficient) among all the accessions considered. One of the aims of this study was to clarify the genetic assessment of Aglianico Nero and Aglianico del Vulture Nero, since they are registered as two different cultivars with distinct varietal codes at the Italian Register of Grape Varieties. Registered Aglianico Nero and Aglianico del Vulture Nero were included in the analyses, compared and used as reference material. Our plants showed that all the accessions tested, independent from the biotype, and the two registered cultivars belong to the same genotype, suggesting that, as reported by the Vitis International Variety Catalogue, a case of synonymy occurred between Aglianico Nero and Aglianico del Vulture Nero. These cultivars could therefore be considered as a single cultivar. Moreover, the AFLP data revealed a partial match between morphological and molecular data, showing that the AFLP molecular method was able to discriminate between different accessions belonging to the same cultivar.